Exploring the implementation of community-based health promotion programs for childhood diarrhea prevention in primary healthcare: A qualitative study - Wahyuni Wahyuni; Hairuddin K; Dian Meiliani Yulis (Edukasi Ilmiah Indonesia, 2026)
Introduction: Childhood diarrhea remains a major public health challenge in low- and middle-income countries despite the widespread implementation of health promotion initiatives through primary healthcare services. While previous studies have largely evaluated intervention effectiveness using quantitative indicators, there is limited evidence on how community-based health promotion programs are implemented in routine primary healthcare settings. This study aimed to explore the implementation of community-based health promotion programs to prevent childhood diarrhoea from multiple stakeholders' perspectives. Research Methodology: A qualitative descriptive study with an interpretive approach was conducted between January and March 2026 in the working area of Bontomangape Primary Health Center, Takalar Regency, Indonesia. Twenty-five purposively selected informants, including healthcare managers, health promotion officers, healthcare professionals, community health volunteers, and mothers of children under five years, participated in semi-structured in-depth interviews. Non-participant observations and document reviews were used to strengthen data triangulation. Data were analyzed using Braun and Clarke's six-phase Reflexive Thematic Analysis supported by NVivo Release 14. Trustworthiness was established through credibility, transferability, dependability, and confirmability. Results: Four interconnected themes emerged: implementation of community-based health promotion activities, perceived program benefits, barriers to implementation, and strategies for program strengthening. Participants reported that health education, home visits, and Posyandu activities improved caregivers' knowledge and preventive practices. However, workforce shortages, limited educational resources, and inconsistent community participation constrained program sustainability. Data saturation was achieved after the twenty-third interview and confirmed through two additional interviews. Conclusion: Community-based health promotion is an essential component of childhood diarrhoea prevention but requires stronger organisational capacity, sustained community engagement, and intersectoral collaboration to maximise its effectiveness. Strengthening primary healthcare systems through context-sensitive, community-centred health promotion strategies may improve program sustainability and help reduce the burden of preventable childhood diarrhoea